Effect of mineral supplementation on milk yield and calf growth of camels in Marsabit district of Kenya - Kuria, S.G.; Gachuiri, C.K.; Wanyoike, M.M.; Wahome, R.G. (2004)
A study was conducted in Ngurunit and Kargi locations of Marsabit district in Kenya to determine the effect of mineral supplementation on milk yield and calf growth of settlement based camels. Two mineral supplements were formulated; one comprised of locally collected, ground bones mixed with locally available natural salt and the other of commercial ingredients. Fifty nine (59) and 56 camels in early lactation and their calves were selected at Kargi and Ngurunit, respectively. Of these, 22 and 21 camels were randomly assigned the commercial supplement while 12 and 11 were assigned the local supplement at Kargi and Ngurunit, respectively. There were 25 and 23 control camels in Kargi and Ngurunit, respectively. Each dam was individually fed 200 g of mineral supplement daily for 190 days. During the data collection period, milk yield measurements were taken at weekly intervals and calves weighed monthly. The results showed that supplemented camels produced higher (P = 0.000) amount of milk than controls in Ngurunit (3.2 ld-1 versus 2.3 ld-1). In Kargi, the mean milk yield for supplemented and control camels were similar (P > 0.05) at 2.6 ld-1. Calves from the supplemented dams grew faster (P = 0.000) than the controls, gaining 441.3 gd-1 and 424.8 gd-1 compared with 275.7 gd-1 and 307.7 gd-1 for controls in Kargi and Ngurunit, respectively. The results suggested that mineral deficiency existed among the Rendille camels. The problem could however be reduced by judicial use of locally available raw material.